Assessment of Organizational Performance: Linking the Motivational Antecedents of Empowerment, Compensation and Organizational Commitment - Ibrahim Garba Muhammad; Haim Hilman Abdullah (International Review of Management and Marketing, 2016)
A growing body of knowledge in social exchange theory has long postulated social exchange interrelationships as the dominant practice within the organization. Specifically, nearly majority of previous studies utilizing social exchange theory concentrates on testing the direct effect of various organizational practices on functional and organizational outcome with little attention towards the intermediate mechanism facilitating such connection. In this vein, this study draws from social exchange theory to investigate the mediating role of organizational commitment on the effect of empowerment and compensation on organizational performance. Data was collected from bank managers using a cross sectional survey and all the direct and indirect propositions were supported. Organizational commitment was found to mediate the effect of empowerment and compensation on organizational performance. The limitations and implications of the study were discussed and area for future studies provided.